Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Berbasis Canva Education di MTs Nurul Izzah - Irmayanti Iramaynti; Nurjannah Nurjannah; Anggy Heriyanti; Mirna Mirna; Fahmita Sari (AKM, 2023)
The purpose of this training and mentoring activity is for teachers to gain new knowledge about making Canva Education-based interactive learning media. This mentoring method is service learning. The type of service learning used is Integration of Service Learning in Subjects, which is a type of community service that is integrated with courses in study programs. In this service, the team will integrate training and assistance in making Canva Education-based learning media with courses in Mathematics Tadris Study Program. The courses that will be in service learning are Mathematics Learning Workshops in odd semesters of the 2021/2022 Academic year. The result of this community service is that this activity provides opportunities for participants to be more productive in teaching, the activities carried out are their needs and the material that has been taught and assumes that the material being taught can assist participants in teaching material to students in class and canva education becomes solutions for teachers in making interactive learning media.